Karakter Agronomi dan Fisiologi Berbeagai Varietas Tanaman Lobak (Raphanus Sativus L.) Dengan Penerapan Sonic Bloom di Dataran Rendah - Ramadhani, Febryanti (Journal of Comprehensive Science, 2024)
Radish plants (Raphanus sativus L.) belong to the category of horticultural plants that are bushy with a taproot. The desire to develop this crop among farmers in Gandasuli Village, South Halmahera Regency is quite high. However, the main obstacle to developing radishes in lowland areas is the relatively high temperature, leading to concerns about crop failure. How to increase plant productivity using sonic bloom technology. This technology uses sound waves and high frequencies without disturbing the surrounding environment. This research aims to understand the agronomic and physiological development of various radish plant varieties that can thrive well without the application of sonic bloom and with the application of sonic bloom, as well as to observe the effect of sonic bloom on these various varieties in lowland areas. The research design is divided into two stages: stage 1, research without using sonic bloom, and stage 2, research using sonic bloom, which employs a Completely Randomized Design (CRD) with 3 treatments and 4 replications. Different variety treatments are P1 = white radish, P2 = long red radish, and P3 = round red radish. The application of sonic bloom, which shows many significant effects on the observed variables, is demonstrated on white radish plants in the variables of plant height at 14 days after planting (HST), number of leaves at 14 and 21 HST, tuber length, fresh weight of the plant's upper part, fresh weight of the tuber, chlorophyll content, and number of stomata at 14 HST.